PENGARUH KOMBINASI SLOW DEEP BREATHING DAN AROMATERAPI LAVENDER TERHADAP PERUBAHAN TEKANAN DARAH - Silvina Wulandari; Siti Rusminarni; Tubagus Erwin (Universitas Aufa Royhan, 2025)
Hypertension is defined as having a systolic blood pressure greater than 140 mmHg and a diastolic blood pressure exceeding 90 mmHg. Based on the 2024 Indonesian Health Survey, the prevalence of hypertension in Lampung Province is 28.3% or 19,843 people among individuals in the ≥15 age group, and 29.7% or 18,762 people among those in the ≥18 age group. This study aims to assess the impact of slow deep breathing combined with lavender aromatherapy on blood pressure levels in hypertensive patients within the Segala Mider Community Health Center area of Bandar Lampung City in 2024. Employing a quantitative approach, the research utilizes a Quasi-Experimental pretest-posttest control group design. The population for this study includes 78 hypertensive patients enrolled in the Prolanis program, with a sample size of 66 respondents per group. Purposive sampling was used to select participants, and statistical analysis was performed using the Paired t-test. The results from the paired t-test analysis revealed a pre-posttest systolic p-value of 0.000 and a diastolic p-value of 0.001 in the treatment group. In contrast, the control group showed a pre-posttest systolic p-value of 0.229 and a diastolic p-value of 0.146. The combination of slow deep breathing and lavender aromatherapy had a significant impact on blood pressure levels in hypertensive patients (p-value of 0.001, which is less than 0.05). It is hoped that this combination could be used as a non-pharmacological approach to lower blood pressure.